Problems of introducing innovative technologies into the educational process in higher educational institutions (MMIT Proceedings, 2025)
This article examines the challenges of integrating innovative technologies into the educational process in higher education institutions, as well as the models implemented at INTI International University (Malaysia) and the International University of Education (TIUE)